2019
DOI: 10.1155/2019/5245184
|View full text |Cite
|
Sign up to set email alerts
|

How May Coexisting Frailty Influence Adherence to Treatment in Elderly Hypertensive Patients?

Abstract: Background Hypertension is considered to be the most common condition in the general population. It is the most important risk factor for premature deaths in the world. Treatment compliance at every stage is a condition for successful antihypertensive therapy, and improving the effectiveness of treatment is a major goal in preventing cardiovascular incidents. Treatment noncompliance and lack of cooperation stem from numerous problems of older age, including frailty syndrome. Objective To evaluate the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
2
11
0
1
Order By: Relevance
“…To date, studies have shown that the median therapeutic adherence to antihypertensive therapy is 55.3% [35]. In the present study, the mean Hill-Bone adherence score was 20.51, which coincides with the results by Uchmanowicz et al [33] and Chudiak et al [34]. However, among hypertension patients living in Palestine the average score on the Hill-Hill-Bone scale was 24.9, which implies a lower adherence rate in comparison with the above studies [36].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To date, studies have shown that the median therapeutic adherence to antihypertensive therapy is 55.3% [35]. In the present study, the mean Hill-Bone adherence score was 20.51, which coincides with the results by Uchmanowicz et al [33] and Chudiak et al [34]. However, among hypertension patients living in Palestine the average score on the Hill-Hill-Bone scale was 24.9, which implies a lower adherence rate in comparison with the above studies [36].…”
Section: Discussionsupporting
confidence: 92%
“…A meta-analysis by Vetrano et al [31] showed that among patients with hypertension, 14% also have frailty syndrome, while frailty syndrome occurs in 46.5% of people over 65 with hypertension [32]. In fact, the most significant component of frailty syndrome turned out to be the physical component [28], which is consistent with the recent findings by Uchmanowicz et al [33]. In contrast, the study by Chudiak et al [34] suggested that for older hypertensive patients the social component of frailty played the most significant role, more likely resulting from poor fitness and diminished everyday life independence.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The prevalence of frailty in community samples ranges from 6 to 11.1% [8][9][10]. Inpatients have a higher prevalence of frailty, ranging from 25 to 65.62% [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of frailty in community samples ranges from 6% to 11.1% [9][10][11]. Inpatients have a higher prevalence of frailty, ranging from 25% to 65.62% [12,13].…”
mentioning
confidence: 99%